Efficacy of Long-Pulsed Nd:YAG Laser for Classic Kaposi's Sarcoma: A Dermoscopic Study - Seher Bostancı; Merve Aygun Alızada; Banu Farabi; Bengu Nisa Akay (Mattioli1885, 2024)
Introduction: Classic Kaposi's sarcoma (CKS) is a chronic and indolent skin tumor. Because CKS has a low mortality rate but can have a significant impact on quality of life, it is important to choose safe, long-term treatments with minimal side effects. Objectives: The aim was to assess the efficacy of long-pulsed Nd:YAG laser therapy in treating CKS based on clinical and dermoscopic observations. Methods: Forty-two nodular lesions from three CKS patients (stage 4) were treated using a long-pulsed Nd:YAG laser with a spot size ranging from 3 to 7 mm, a fluence of 200-250 j/cm2, and a pulse duration lasting between 10 and 20 milliseconds in one or two sessions. Patients were photographed clinically and dermoscopically before the procedure, immediately after the procedure, and at 1, 6, and 12 months after the procedure. Results: All participants displayed significant clinical and dermoscopic improvements, and all lesions healed within 2-3 weeks, resulting in only minor atrophic scars. No instance of recurrence was found among any of the patients during the 1-year follow-up. Conclusions: Nd:YAG laser therapy may prove to be an effective therapeutic alternative for both early and advanced-stage CKS, specifically in instances of stubborn cutaneous lesions or patients receiving systemic therapy. The treatment results in quick improvement, typically within 2-3 weeks, and is well tolerated. Nd:YAG laser therapy could provide potential benefits for HIV-positive patients as it is free from immunosuppression, easy to apply to recurring lesions, and demonstrates overall effectiveness and safety.